The Impact of the Epidemiological Situation Resulting From COVID-19 Pandemic on Selected Aspects of Mental Health Among Patients With Cancer–Silesia Province (Poland) - Grajek, Mateusz; Białek-Dratwa, Agnieszka (Frontiers in Psychology, 2022)
Objective: The study aimed to assess the level of disease acceptance as well as the well-being and emotions that accompany cancer patients during the COVID-19 pandemic. Material and methods: The study involved 1000 patients of the oncology centers (Silesia, Poland). The following questionnaires were used for the study: WHO-5 - Well-Being Index, BDI – Beck Depression Inventory, disease acceptance scale, and proprietary multiple-choice questions regarding the impact of the epidemic situation on the respondents' lives so far. The questionnaire study was conducted twice: in March-October 2020 (the beginning of the COVID-19 pandemic in Poland) and March-October 2021 (renewed tightening of sanitary restrictions in Poland). The differences between the given periods were statistically analyzed. Results: At the time of the study, the respondents felt mainly anxiety related to the possibility of contracting COVID-19, the possibility of infecting a loved one, or staying in quarantine. Anxiety was also caused by the vision of poorer access to health services. Along with the duration of the epidemic, the acceptance of neoplastic disease has decreased and the incidence of depressive symptoms has increased. Conclusions: The well-being of the respondents deteriorated significantly during the pandemic. The respondents, in their daily functioning, were mainly accompanied by anxiety. The risk of depression has increased and the acceptance of the disease has decreased significantly.